Jordanian women's dissatisfaction with childbirth care. (25th April 2014) - Mohammad, K.I.; Alafi, K.K.; Mohammad, A.I.; Gamble, J.; Creedy, D.
<x xml:space="preserve">Abstract</x> Background Dissatisfaction with childbirth care can have a negative impact on a woman's health and well‐being, as well as her relationships with her infant. Aim To investigate the prevalence and associated factors of dissatisfaction with intrapartum care by Jordanian women. Method A descriptive cross‐sectional study was used. Participants (n = 320) who were 7 weeks post‐partum were recruited from five maternal and child health centres in Irbid city in northern Jordan. Participants provided personal and obstetric information, and completed the Satisfaction with Childbirth Care Scale. Results The majority of women (75.6%) were dissatisfied with their intrapartum care. Dissatisfaction was associated with the attendance of unknown and unwanted persons during childbirth, experiencing labour as more painful than expected, and perceptions of inadequate help from healthcare providers to manage pain during labour. Limitations Findings are limited to Jordanian women accessing public sector perinatal health services. Conclusion The high percentage of women reporting dissatisfaction with intrapartum care in this study is of concern. Women's perception of pain and expectations of staff during labour and birth need to be addressed through education and improved communication by staff. Implications for Nursing and Health Policy Development of national evidence‐based policies and quality assurance systems would help reduce the rate of obstetric interventions and give greater emphasis to respect for women's preferences during labour and birth.